2021
DOI: 10.1038/s41598-021-01066-z
|View full text |Cite
|
Sign up to set email alerts
|

A duplicated copy of id2b is an unusual sex-determining candidate gene on the Y chromosome of arapaima (Arapaima gigas)

Abstract: Arapaima gigas is one of the largest freshwater fish species of high ecological and economic importance. Overfishing and habitat destruction are severe threats to the remaining wild populations. By incorporating a chromosomal Hi-C contact map, we improved the arapaima genome assembly to chromosome-level, revealing an unexpected high degree of chromosome rearrangements during evolution of the bonytongues (Osteoglossiformes). Combining this new assembly with pool-sequencing of male and female genomes, we identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…This is consistent with our observation that Id1/2/3 and Smad6/7 are expressed in response to Gdf6Y, independent of cell type. Arapaima gigas provided evidence for the involvement of ID genes in sex determination in teleost species with a Y-chromosomal id2b duplicate being its SD gene (Adolfi et al 2021). In N. furzeri, id3 is positively selected like gdf6Y, suggesting a potential co-evolution (Reichwald et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with our observation that Id1/2/3 and Smad6/7 are expressed in response to Gdf6Y, independent of cell type. Arapaima gigas provided evidence for the involvement of ID genes in sex determination in teleost species with a Y-chromosomal id2b duplicate being its SD gene (Adolfi et al 2021). In N. furzeri, id3 is positively selected like gdf6Y, suggesting a potential co-evolution (Reichwald et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The run produced 105 million read pairs for the male pool library and 96 million read pairs for the female pool library. Reads from the male and female pools were analysed as previously described (Adolfi et al, 2021;Imarazene et al, 2021;Pan, Feron, et al, 2021), using the pooled sequencing analyses for sex signal (PSASS; https://github.com/SexGe nomic sTool kit/PSASS), a software that compares pooled sequencing data sets from two sexes, and our Pacific halibut assembly as a reference assembly. PSASS was run with default parameters to compute three metrics in 50 kb nonoverlapping windows over the Pacific halibut genome: (1) F ST between males and females over the window, (2) density of sex-specific SNPs, defined as SNPs heterozygous in one sex and homozygous in the other sex, and (3) read depth for each sex.…”
Section: Pool Genome Sequencing (Poolseq) and Analysismentioning
confidence: 99%
“…The first minimally invasive and accurate method for determining genetic markers was presented by Adolfi et al (2021). They performed a transcriptome analysis and protein structure predictions, which confirmed that the id2bbY gene is the main candidate gene for sex determination since it is expressed in the gonads of juvenile individuals.…”
Section: Techniques For Sexual Identificationmentioning
confidence: 90%
“…Among the proposals related to marker for sex identification in A. gigas, Cavalcante et al (2020) evaluated methods based on sequences of k consecutive nucleotides (k-mer), demonstrating that this interesting and low-complexity sexual identification technique searches for repeat regions on represented or under-represented nucleotides in one of the two sexes (Ezaz & Deakin, 2014). The first method for determining genetic markers that met the necessary accuracy and was minimally invasive was that of Adolfi et al (2021), who performed a transcriptome analysis and protein structure predictions, which confirmed that the id2bbY gene is the main gene candidate for sex determination, since it is expressed in gonads of juvenile individuals. The method used was minimally invasive and only required the extraction of a small sample of the fin.…”
Section: Techniques For Sexual Identificationmentioning
confidence: 99%